2019
DOI: 10.1186/s13058-019-1115-2
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA alterations and benefit with neratinib: analysis from the randomized, double-blind, placebo-controlled, phase III ExteNET trial

Abstract: BackgroundNeratinib is an irreversible pan-HER tyrosine kinase inhibitor that inhibits PI3K/Akt and MAPK signaling pathways after HER2 receptor activation. The ExteNET study showed that neratinib significantly improved 5-year invasive disease-free survival (iDFS) in women who completed trastuzumab-based adjuvant therapy for early breast cancer (EBC). We assessed the prognostic and predictive significance of PIK3CA alterations in patients in ExteNET.MethodsParticipants were women aged ≥ 18 years (≥ 20 years in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…In our cohort, patients with PIK3CA mutation were more frequently postmenopausal and showed more frequently HR-positive disease. However, the association with hormone receptor-status is not consistent across studies (3,8,9). According to intrinsic subtype, in our study, Luminal A tumors showed the highest frequency of PIK3CA mutation, although the distribution of PIK3CA mutation across intrinsic subtypes was not statistically significant.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In our cohort, patients with PIK3CA mutation were more frequently postmenopausal and showed more frequently HR-positive disease. However, the association with hormone receptor-status is not consistent across studies (3,8,9). According to intrinsic subtype, in our study, Luminal A tumors showed the highest frequency of PIK3CA mutation, although the distribution of PIK3CA mutation across intrinsic subtypes was not statistically significant.…”
Section: Discussioncontrasting
confidence: 88%
“…We did not find any prognostic impact of PIK3CA gene mutation in the overall study cohort. This result is concordant with data from other adjuvant trials showing no association between PIK3CA mutation and long-term outcome (7)(8)(9). Moreover, in the NSABP B-31 and FinHER studies, PIK3CA mutation was not predictive of reduced benefit from adjuvant trastuzumab (7,8).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Preclinically, neratinib inhibited proliferation in HER2 -amplified, PIK3CA -mutant tumor cell lines [73], and inhibited tumor growth in a HER2-positive, PIK3CA -mutant patient-derived xenograft model [119]. In the positive phase III ExteNET study, which compared 1 year of neratinib versus placebo given in the adjuvant setting after standard trastuzumab-based therapy, absolute risk reduction was associated with neratinib treatment of patients with PIK3CA -mutated or -amplified cancers, although this reduction was not statistically significant [120]. In the first 125 patients from the SUMMIT basket trial for HER2 -mutant, metastatic solid tumors who were treated with neratinib monotherapy, PIK3CA mutations were more prevalent in patients who were on treatment for <24 weeks than those who were on for ≥24 weeks, although this difference was not statistically significant [81].…”
Section: Resistance To Lapatinib and Neratinibmentioning
confidence: 99%
“…Therefore, circulating tumor DNA (ctDNA) analysis has been widely employed as a noninvasive approach to detect PIK3CA mutation status [28]. Comparing with archival tumor samples, ctDNA analysis is a more illustrative and less invasive technique to assess the mutational status and heterogenicity throughout the treatment [29]. In our methods, we collect the responsive and survival data according to the PIK3CA mutation status in ctDNA analysis, which is broadly applied to detect the gene mutation status in cancers.…”
Section: Biomed Research Internationalmentioning
confidence: 99%